2013
DOI: 10.1037/a0033069
|View full text |Cite
|
Sign up to set email alerts
|

Spared and impaired aspects of motivated cognitive control in schizophrenia.

Abstract: The ability to upregulate cognitive control in motivationally salient situations was examined in individuals with schizophrenia (patients) and healthy controls. Fifty-four patients and thirty-nine healthy controls were recruited. A computerized monetary response conflict task required participants to identity a picture, over which was printed a matching (congruent), neutral, or incongruent word. This baseline condition was followed by an incentive condition, in which participants were given the opportunity to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 82 publications
(128 reference statements)
2
29
2
Order By: Relevance
“…Different from our previous study (Mann et al, 2013) showing a reduced reward context effect in schizophrenia but an intact reward cue effect, we found that individuals with schizophrenia showed no significant differences from the HC in either reward cue or reward context effects. The discrepancy between two studies may be due to methodological differences.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Different from our previous study (Mann et al, 2013) showing a reduced reward context effect in schizophrenia but an intact reward cue effect, we found that individuals with schizophrenia showed no significant differences from the HC in either reward cue or reward context effects. The discrepancy between two studies may be due to methodological differences.…”
Section: Discussioncontrasting
confidence: 99%
“…The discrepancy between two studies may be due to methodological differences. The clearest difference in the current study from Mann et al (2013) is a modification of the task paradigm by adopting a mixed state-item fMRI design. Thus, the current study included a jittered period between the presentation of cues and target phase while our prior behavioral study did not include such a jittered period; the target phase was followed right after the presentation of each cue.…”
Section: Discussionmentioning
confidence: 97%
“…The SCZ reported significantly greater anhedonia across almost all of the self-report measures. However results for these self-report measures in a largely overlapping subset were previously reported in (Mann et al, in press). The SCZ reported significantly greater levels of depression.…”
Section: Resultssupporting
confidence: 68%
“…These individuals were participating in a larger study on motivation and reward processing in schizophrenia, and the majority of these participants also participated in the study described in (Mann, Footer, Chung, Driscoll, & Barch, in press). Fifty-three of the SCZ were taking antipsychotic medications.…”
Section: Methodsmentioning
confidence: 99%
“…Patients were able to speed their responses when presented with specific cues about winning reward and to a certain extent could speed their responses on trials in the reward "context" even when they could not earn money, an effect thought to reflect the maintenance of reward information through proactive control mechanisms. However, the individuals with schizophrenia showed a significantly smaller incentive context effect than controls, suggesting a reduction in the use of proactive control and a greater reliance on the use of "just-in-time," reactive control strategies (Mann et al 2013). To date, there are no published fMRI studies examining whether or not incentives modulate DLPFC activity during cognitive control or working memory tasks in schizophrenia.…”
Section: Schizophreniamentioning
confidence: 97%